Stratification variability in the Yucatan Channel and its relationship with the Loop Current System - Higuera-Parra, Susana; Moreles, Efraín; Olvera-Prado, Erick R.; Zavala-Hidalgo, Jorge (Frontiers in Marine Science, 2023)
The non-seasonal stratification variability in the upper 400 m of the Yucatan Channel (YC) and its relationship with the Loop Current System is studied based on the analysis of long-term timescales not yet resolved in observational studies. Daily outputs from a 22-year free-running simulation performed with the HYbrid Coordinate Ocean Model were used, and the variability modes of the squared buoyancy frequency were estimated using Empirical Orthogonal Functions. Intrinsic ocean dynamics is the primary determinant of the dominant spatial and temporal variability of hydrography and dynamics in the YC. The leading mode, described by a vertical dipole at the western YC section with timescales of 1.5-7.5 years, is mainly determined by the Yucatan Current (YCu) variability. There is a strong connection between YCu dynamics, the upper YC hydrography, the Loop Current (LC) intrusion into the Gulf of Mexico, the detachment of Loop Current Eddies (LCEs), and cyclonic anomalies surrounding the LC. Intense eastward displacements of the YCu are associated with intense stratification anomalies in the western YC, the presence of cyclonic anomalies surrounding the LC southwest margin, detachments of LCEs with larger-than-average diameter, and intense LC retreat; before these eddy detachments, the LC metric values are lower than their average ones. Atmospheric forcing induces more complexity in YC dynamics and the Loop Current System; it produces a significant high-frequency signal that modifies their low-frequency behavior. The relationships found in this work could contribute to a better understanding of the upwelling development on the eastern Yucatan shelf.